TINJAUAN YURIDIS TERHADAP PELAKU USAHA TV KABEL MENDIRIKAN USAHA PADA SARANA FASILITAS UMUM DI KOTA SAMARINDA - Eni Rahmawati dan Ekawati (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2020)
This research was conducted at Samarinda City, East Kalimantan Province, Indonesia. This study aims to determine the regulation and legal liability of cable TV business operators who establish businesses in public facilities in Samarinda City. The method that used in this research is a normative legal method that is studying document studies, using various legal materials such as statutory regulations, non-legal materials and in the form of opinions from scholars. The legal material in this study is sourced from primary legal materials, secondary legal materials, and non-legal materials.From the results of this study it can be concluded that the legal arrangements for businesses that set up cable TV businesses in public facilities in Samarinda City are contained in Law No.30 of 2009 concerning Electricity Article 48 Paragraph (1). The legal responsibility of cable TV business operators who establish businesses in public facilities in Samarinda against the Samarinda city government is that if an adverse incident occurs that results in pollution and / or environmental damage is considered an illegal act. To overcome various legal issues regarding cable TV business operators, the Samarinda City Regional Government should make a regional regulation specifically regulating the supervision of Cable TV business licensing in Samarinda City because with the regional regulation it is expected to minimize the number of violations of the law, and should Cable TV business operators no longer use electricity network supporting poles which are public facilities owned by the city government, it is far better if cable cable business operators are planted on the ground level, so as to minimize the existence of electrical zippers, fires due to short electrical current and do not disturb the aesthetic of this city.